Equity and growth in a globalizing world - Kanbur, S. M. Ravi.; Spence, Michael (Washington, DC : Commission on Growth and Development/World Bank, 2010)
It has been prepared to evaluate the state of knowledge on the relationship between poverty, equity within nations, and the policy frameworks that can best address distributional concerns as the basis for a growth strategy.
Includes bibliographical references and index.
uaj 25/04/13
Loans
Keywords: Economic development; Equality; Economic policy; Globalization; International economic relations